Concrete cover separation of reinforced concrete beams strengthened with near-surface mounted method: Mechanics based design approach. Issue 7 (May 2019) - Shukri, Ahmad Azim; Ibrahim, Zainah; Hashim, Huzaifa
The primary mode of premature failure for near-surface mounted strengthened beams is the concrete cover separation. Due to its complexity, most of the prediction methods for concrete cover separation tend to be empirical based, which can limit their usage to specific near-surface mounted strengthening configurations. In response to that, this article presents a mechanics-based design which uses the moment-rotation approach and the global energy balance approach which is less reliant on empirical formulations, as the mechanics of reinforced concrete beam such as tension stiffening and propagation of concrete cover separation debonding crack are directly simulated rather than empirically derived. The proposed design procedure was validated against published experimental results of reinforced concrete beams strengthened with near-surface mounted carbon fibre–reinforced polymer bars, near-surface mounted carbon fibre–reinforced polymer strips or side-near-surface mounted carbon fibre–reinforced polymer bars and show good accuracy. As it is less reliant on empirical formulations, the proposed design procedure should be applicable to various near-surface mounted reinforcement configurations and materials.